Principles of distributed systems 15th International conference, OPODIS 2011, Toulouse, France, December 13-16, 2011 : proceedings - FAnta, Antonio Fernández; Lipari, Giuseppe 1971-; Roy, Matthieu (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 15th International Conference on Principles of Distributed Systems, OPODIS 2011, held in Toulouse, France, in December 2011. The 26 revised papers presented in this volume were carefully reviewed and selected from 96 submissions. They represent the current state of the art of the research in the field of the design, analysis and development of distributed and real-time systems.